2018
DOI: 10.3389/fendo.2018.00709
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of NLRP3 Inflammation-Related Gene Promotor Methylation as Well as Mediating Effects on T2DM and Vascular Complications in a Southern Han Chinese Population

Abstract: Objective: To explore the association between the methylation levels in the promoter regions of the NLRP3, AIM2, and ASC genes and T2DM and its vascular complications in a Southern Han Chinese population and further analyze their interaction and mediating effects with environmental factors in T2DM.Methods: A case-control study was used to determine the association between population characteristics, the methylation level in the promoter region of the NLRP3, AIM2, and ASC genes and T2DM and vascular complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…DNA methylation‐mediating effects were mostly studied with respect to the occurrence and development of cardiovascular and other diseases . The conclusions were similar to the present study in that DNA methylation could play a mediating role in the development of diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…DNA methylation‐mediating effects were mostly studied with respect to the occurrence and development of cardiovascular and other diseases . The conclusions were similar to the present study in that DNA methylation could play a mediating role in the development of diseases.…”
Section: Discussionsupporting
confidence: 89%
“…DNA methylation-mediating effects were mostly studied with respect to the occurrence and development of cardiovascular 29,30 and other diseases. 15,31 The conclusions were similar to the present 32 The increase of S-adenosine homocysteinemia is related to DNA hypomethylation, 33 and Hcy is a byproduct of the methyltransferase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a lower level of total methy-lation in NLRP3 promoter was associated with a 17.78-fold increase in risk for micro-and macrovascular complications in T2D. 30 As discussed earlier, the CpG sites in the gene promoter region were usually adjacent to transcription factor binding sites. As such, hypomethylation in the promoter may cause increased gene expression.…”
Section: Discussionmentioning
confidence: 87%
“…Additional path model analysis of mediating effects was used to evaluate associations among age, OGTT and adverse outcomes in GDM patients. We used to employ this method in our previous studies to identify mediating effect among age, gene promoter methylation level and type 2 diabetes mellitus (T2DM) vascular complications (22). Because adverse outcome was binary variable, we used Bayesian analysis method to get the standardized regression coefficients a, b, c ′ and c which identify relationships between variables (23) (in the model the variables are a, direct association between independent and mediator variable; b, direct association between mediator and dependent variable; c ′ , direct association between independent and dependent variable; c, total association between independent and dependent variables; ab, indirect effect; c ′ , direct effect; c, total effect; and (ab/c) * 100%, mediating effect generated by the mediator variable in the dependent variable outcome caused by the independent variable).…”
Section: Discussionmentioning
confidence: 99%